Analisis Buku Ajar Sejarah Kebudayaan Islam Kelas IV Madrasah Ibtidaiyah (MI) Menurut Perspektif Badan Standar Nasional Pendidikan - Willy Akmansyah Lubis; Arsy Putri (YASIN, 2026)
Islamic Cultural History (Sejarah Kebudayaan Islam, SKI) textbooks have been widely used as primary learning resources in Madrasah Ibtidaiyah; however, studies that specifically analyze the feasibility level of Grade IV SKI textbooks based on the criteria of the Badan Standar Nasional Pendidikan (BSNP) remain relatively limited. This study aimed to analyze the feasibility of the Grade IV Islamic Cultural History textbook for Madrasah Ibtidaiyah published by the Ministry of Religious Affairs of the Republic of Indonesia in terms of content, presentation, language, and graphics in accordance with BSNP standards. The study employed a qualitative approach with a descriptive research design through a literature study. Data were obtained through document analysis using an assessment instrument developed based on BSNP textbook feasibility criteria and were analyzed descriptively by assigning scores to each assessment indicator. The results showed that the Grade IV Islamic Cultural History textbook for Madrasah Ibtidaiyah obtained an overall score of 92.10, which falls into the “highly feasible” category, with high achievement in the content, language, presentation, and graphical aspects. These findings contribute to the development of evaluation practices for Islamic education teaching materials and reaffirm the importance of applying national standards in quality assurance for textbooks. The study concludes that the Grade IV SKI textbook for Madrasah Ibtidaiyah is suitable for use as a learning resource and recommends that educators and education policymakers continue to evaluate and develop textbooks in accordance with BSNP standards to improve the quality of learning in madrasahs.